TRACING SOME SUPPORT MECHANISMS IN MUSIC FOR THE MOTHER TONGUE EXPERIENCE (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper examines the use of music as a support system in mother tongueacquisition among children. By so doing, the paper traces some of the ways inwhich language and music interact in order to support competencedevelopment in the former. The question here regards the depth ofinvolvement of musical activities in the language process. This research focuseson some Luo songs and games for children. Through observation andinvestigation of primary and secondary sources, a number of musical activitiesand songs have been investigated to establish the depth of this influence uponlanguage learning, including: role plays, lullabies, children‟s games, andprogrammed and creative dances. Music has been integrated in educationprogrammes as a learning resource for early language learning and teaching.The main reason for this is that music provides the learner with an experientialopportunity to develop competence in the field of learning with inducedpleasure that sustains the drive to learn. As the organization of the soundstimuli, the interplay between rhythm and pitch, music results in a meaningfulobject (work of art) whose purpose goes beyond just the production of sound.As a multi-media activity, it involves the use of several senses: sight, touch,hearing and speech. During musical activities, elements of language such asvocabulary, sentence structure and meaning are integrated into the activities.This way, the children learn with less stress and more pleasure. The results ofthis research are intended to agitate towards more concern in policy makingfor the use of music in the language curriculum for the learners enrolled in theearly childhood programmes.